Pemberdayaan Literasi Aksara Kelas dalam Meningkatkan Pembelajaran Bahasa Indonesia di MTsS Jabal Nur Paloh Lada - Sundana, Lina; Diana, Novi; Istiqamah; Yoga, Sahri Nova; Rayluna, Naufa (Catimore: Jurnal Pengabdian Kepada Masyarakat, 2024)
This service aims to increase literacy interest in building a strong knowledge base and equipping students to face increasingly complex future challenges. During this activity, the methods used were lecture methods and simulation of learning media to students. The results of this service contribute to fostering literacy in students as an initial foundation for students' intellectual growth and creativity in improving Indonesian language learning. The materials used in this program include various types of media, including posters featuring rhymes, poetry, motivational messages, as well as educational tools such as scrapbooks, pop up books, and game-based learning media.